Evaluation of delivery of enteral nutrition in mechanically ventilated Malaysian ICU patients - Yip, K.F.; Rai, V.; Wong, K.K. (BioMed Central, 2014)
Background: There are numerous challenges in providing nutrition to the mechanically ventilated critically ill ICU patient. Understanding the level of nutritional support and the barriers to enteral feeding interruption in mechanically ventilated patients are important to maximise the nutritional benefits to the critically ill patients. Thus, this study aims to evaluate enteral nutrition delivery and identify the reasons for interruptions in mechanically ventilated Malaysian patients receiving enteral feeding. Methods: A cross sectional prospective study of 77 consecutive patients who required mechanical ventilation and were receiving enteral nutrition was done in an open 14-bed intensive care unit of a tertiary hospital. Data were collected prospectively over a 3 month period. Descriptive statistical analysis were made with respect to demographical data, time taken to initiate feeds, type of feeds, quantification of feeds attainment, and reasons for feed interruptions. There are no set feeding protocols in the ICU. The usual initial rate of enteral nutrition observed in ICU was 20 ml/hour, assessed every 6 hours and the decision was made thereafter to increase feeds. The target calorie for each patient was determined by the clinician alongside the dietitian. The use of prokinetic agents was also prescribed at the discretion of the attending clinician and is commonly IV metoclopramide 10 mg three times a day. Results: About 66% of patients achieved 80% of caloric requirements within 3 days of which 46.8% achieved full feeds in less than 12 hours. The time to initiate feeds for patients admitted into the ICU ranged from 0-110 hours with a median time to start feeds of 15 hours and the interquartile range (IQR) of 6-59 hours. The mean time to achieve at least 80% of nutritional target was 1.8 days +/- 1.5 days. About 79% of patients experienced multiple feeding interruptions. The most prevalent reason for interruption was for procedures (45.1%) followed by high gastric residual volume (38.0%), diarrhoea (8.4%), difficulty in nasogastric tube placement (5.6%) and vomiting (2.9%). Conclusion: Nutritional inadequacy in mechanically ventilated Malaysian patients receiving enteral nutrition was not as common as expected. However, there is still room for improvement with regards to decreasing the number of patients who did not achieve their caloric requirement throughout their stay in the ICU.